Research On Service Quality Improvement Based on Text Analysis and Semi-Structured Interviews: A Study on Mandarin Oriental WFJ Beijingmobar - Shi, Zhiheng; Liu, Zehua; Shen, Huawen (Journal of Ecohumanism, 2024)
The service quality, which always is defined based on the consumer’s assessment has changed into an element of priority for guests and consumers. With the development of the hospitality industry and the impact of COVID-19, the importance of service quality has become more obvious for both consumers and servicers. The study takes Mandarin Oriental WFJ BeijingMoBar as the study object, evaluates the service quality of MoBar through text analysis and interview research methodologies to summarize customers’ perceptions based on the SERVQUAL model, and explores the potential shortcomings. Partial research results that the majority of consumers show positive emotions according to the data. The study also summarizes two major shortcomings of MoBar at the same time: the insufficiency of professional knowledge of wine for service staff, and the negative impacts on service quality caused by the over-tension of the staff. The study gives three suggestions for improvement: enriching employees’ knowledge of wine in various aspects and at multiple levels, reducing the dependence on interns, and reducing employees’ work pressure.